The Interactive Effect of Internal and External Factors on a Proactive Environmental Strategy and its Influence on a Firm's Performance - Mengüç, Bülent (Journal of business ethics, 2010)
While the literature on the effective management of business and natural environment interfaces is rich and growing, there are still two questions regarding which the literature has yet to reach a definitive conclusion: (1) what is the interactive effect between internal and external drivers on a proactive environmental strategy (PES)? and (2) does a PES influence firm's performance? Drawing on the resource-based view for the internal drivers’ perspective and institutional and legitimacy theories for the external drivers’ perspective, this study suggests that the effect of entrepreneurial orientation on a PES is moderated by the intensity of government regulations and customers’ sensitivity to environmental issues. The authors also examine the relationship between the PES and a firm's performance in terms of sales and profit growth. Implications are discussed regarding the role of a PES in achieving a competitive advantage in the marketplace.